Technical variation in affixing hamstring grafts to the tibia in ACL reconstruction - Danieli, Marcus Vinicius; Fernandes Guerreiro, João Paulo; Queiroz, Alexandre Oliveira; Padovani, Carlos Roberto [UNESP] (FapUNIFESP (SciELO), 2018)
Purpose: To present a technical variation in tibial fixation of quadruple hamstring grafts during anatomic reconstruction of the anterior cruciate ligament (ACL). The secondary purpose was to decrease the costs associated with this procedure. Methods: Twenty patients who underwent ACL reconstruction were selected. A tibial tunnel was constructed using standard techniques, and a femoral tunnel was anatomically created using the outside-in technique. The hamstring autograft was passed (with its bend) into the tibial tunnel and affixed to the tibia using the suspensory technique and a simple staple. Femoral fixation was performed using a titanium interference screw. The patients underwent postoperative evaluations at 0, 3, 6 and 12 months using the subjective International Knee Documentation Committee (IKDC) form and Lysholm knee scores. Results: The IKDC and Lysholm score results improved over time (p < 0.001) without major complications. The cost of the procedure could be reduced by using lower-cost hardware (staples). Conclusion: The proposed technique for anatomic ACL reconstruction using inverted hamstring grafts with their bend in the tibial tunnel, suspension-type fixation using a staple demonstrated good to excellent results after 1 year of follow up, with lower aggregate costs.
Keywords: Anterior cruciate ligament reconstruction; Orthopedic fixation devices; Tendons